Choice experimental assessment of the cost of sea level rise in the context of global climatic change: Evidence based on private insurance packages in Ghana - Chineboaba A. Afful; Aklesso Y.G. Egbendewe (Scientific African, 2025)
This research seeks to estimate the cost of sea level rise in the context of global climatic change with evidence from the coastal West African country of Ghana. The willingness to pay for proposed flood insurance packages which translates into private demand of protection against damages caused by sea level is used to estimate the total out of sample cost faced by economic agents living across the region. The Choice Modeling (CM) approach which has its foundation from the Random Utility Theory (RUT) originally developed by Marschak (1960), is used in the estimation of the total sea level rise cost from private market perspective. The results show that gender, knowledge of sea level rise, ability to cope with sea level rise and being displaced by sea level rise are the key factors that govern one’s decision to choose an insurance package or not. Also, men are more likely to choose insurance packages and pay more as compared to women. The estimated average willingness to pay for all packages is 1830 local currency units (LCU). In addition, the average willingness to pay for all packages for the total households (about 1808 households) of the study area is approximately 3308,640 LCU. The study encourages flood insurance purchase as a private solution to sea level rise which may require subsidies from the government for the coastal dwellers to afford the proposed packages. In particular, vulnerable groups such as households led by women may need subsidies from public funds to adapt.